Nurses' knowledge of advance directives and perceived confidence in end‐of‐life care: a cross‐sectional study in five countries. Issue 3 (28th January 2016) - Coffey, Alice; McCarthy, Geraldine; Weathers, Elizabeth; Friedman, M. Isabel; Gallo, Katherine; Ehrenfeld, Mally; Chan, Sophia; Li, William H.C.; Poletti, Piera; Zanotti, Renzo; Molloy, D. William; McGlade, Ciara; et al.
Abstract : Nurses' knowledge regarding advance directives may affect their administration and completion in end‐of‐life care. Confidence among nurses is a barrier to the provision of quality end‐of‐life care. This study investigated nurses' knowledge of advance directives and perceived confidence in end‐of‐life care, in Hong Kong, Ireland, Israel, Italy and the USA using a cross‐sectional descriptive design ( n  = 1089). In all countries, older nurses and those who had more professional experience felt more confident managing patients' symptoms at end‐of‐life and more comfortable stopping preventive medications at end‐of‐life. Nurses in the USA reported that they have more knowledge and experience of advance directives compared with other countries. In addition, they reported the highest levels of confidence and comfort in dealing with end‐of‐life care. Although legislation for advance directives does not yet exist in Ireland, nurses reported high levels of confidence in end‐of‐life care.